Career Center Application as Centralization of Development and Career Guidance for Students-Alumni of the Universitas Pembangunan Nasional “Veteran” Jawa Timur - Pratama, Arista; Mukaromah, Siti (Nusantara Science and Technology Proceedings, 2023)
Universitas Pembangunan National "Veteran" Jawa Timur is expected to produce competent graduates to fill the needs of the world of work and society with optimal quality standards. Quality graduates are a significant factor determining the superiority of the Indonesian nation's human resources at the global level. UPN "Veteran" Jawa Timur is required to continue and improve the quality of education and ensure the readiness of graduates to face challenges in the world of work. This research aims to develop a website-based Career Center (PUSAKA) application using artificial intelligence to centralize coaching and career development for UPN "Veteran" of Jawa Timur student alumni. The Career Center Application (PUSAKA) makes it easier to search for and find job opportunities that suit college graduates' fields of study, skills, and interests. Development of the Career Center (PUSAKA) application uses PHP natural language processing programming and MySQL as the database. Development of the Career Center (PUSAKA) application model uses the ICONIX Process. The website-based Career Center (PUSAKA) application using artificial intelligence has several features, namely student-alumni profiles, a career consultation ChatBot, job-internship-training vacancy information, and recruitment based on job matching according to the user's skills, interests, and experience. This research is helpful for UPN "Veteran" Jawa Timur's students and alumni for career guidance and development in the form of knowledge, skills, and interest in forming superior and quality human resources in the world of work. UPN "Veteran" Jawa Timur can form human resources with integrity and a high professional spirit for Indonesia globally.